Developing College English Writing Course by Using Length Approach Combined with Task-based Learning to Enhance Writing Skills of Non-English Major Students in Xi’an University - Kang , Xiaoqian; Kotchasit, Sombat; Nilnopkoon, Phithack (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: This study was a research and development. The objectives of this research were 1) To study the background information relevant to developing College English Writing Courses by using the Length Approach combined with Task-based Learning to Enhance the Writing Skills of Non-English major students.2) To develop a College English Writing Course by using the Length Approach combined with Task-based Learning to Enhance the Writing Skills of non-English major students. 3) To study the effectiveness of implementing a College English Writing Course by using the Length Approach combined with Task-based Learning. Materials and Methods: The samples were 40 first-year students, non-major English at Xi’an University, the People's Republic of China. They were derived by cluster random sampling. The instruments used in this research were 1) a College English Writing Course using the Length Approach combined with Task-based Learning and its lesson plans, 2) an English writing skills test with .78 of reliability, and 3) a students’ satisfaction questionnaire with .75 of reliability. The statistics used to analyze data included mean, standard deviation, and t-test for one sample. Results: After learning through College English Writing Course by using the Length Approach combined with Task-based Learning, the English Writing skills of students were higher than before learning with a statistical significance of .05 level, and (2) the student's satisfaction with College English Writing Course by using Length Approach combined with Task-based Learning was at a high level. Conclusion: Learning through College English Writing Course by using the Length Approach combined with Task-based Learning has both theoretical and practical significance, Firstly, the research proposes the role of the Length Approach and task-based learning based on output in second language acquisition. Secondly, it is confirmed in this study that language use and production is an essential part of language learning and that one can learn a Second language through using the language. Length Approach and task-based learning are suitable for daily teaching because they can enhance English writing skills for non-English major students and be helpful in the acquisition of a second language.